Simplified method for calculating ground lateral displacement induced by foundation pit excavation. Issue 7 (23rd March 2020) - Cheng, Kang; Riqing, Xu; Ying, Hong-wei; Cungang, Lin; Gan, Xiaolu
Abstract : Purpose: The purpose of this study is to present a simplified analytical method to estimate ground lateral displacement due to excavation. Excavations of foundation pit will inevitably lead to soil movements that may adversely impact surrounding facilities or structures. Thus, estimation of the ground displacement induced by excavation is essential in engineering practice. Design/methodology/approach: Based on a theory of elastic mechanics, a simplified analytical method for predicting the ground lateral displacement resulting from foundation pit excavation is proposed. Findings: As the distance from the soil to the supporting structure increases, the maximum ground lateral displacement decreases nonlinearly but at a reduced rate. Poisson's ratio of soil has a mild influence on the ground lateral displacement, whereas the influence of the supporting structure's deflection modes is significant. Originality/value: The advantage of the proposed simplified analytical method lies in that it considers the supporting structure's arbitrary deflections, giving it wider practical applicability than previous methods.